2009
DOI: 10.1177/1553350609342988
|View full text |Cite
|
Sign up to set email alerts
|

Barbed Suture for Gastrointestinal Closure: A Randomized Control Trial

Abstract: In an effort to make laparoscopic suturing more efficient, the V-Loc advanced wound closure device (Covidien, Mansfield, MA) has been produced. This device is a self-anchoring barbed suture that obviates the need for knot tying. The goal of this initial feasibility study was to investigate the use of the barbed suture in gastrointestinal enterotomy closure. A randomized study of 12 pigs comparing enterotomy closure with barbed versus a nonbarbed suture of similar tensile strength was performed. To this end, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 11 publications
1
91
0
1
Order By: Relevance
“…Recently, an absorbable unidirectional barbed suture has become available (V-Loc™180, Covidien, Mansfield, MA) ( Figure-1). This suture has been used for skin and soft tissue closures, gynecologic procedures, and bowel anastomosis in a porcine model (6)(7)(8). Anastomoses using standard monofilament for running closure requires frequent re-tightening, with some surgeons relying on the assistant to follow the suture to maintain tension.…”
mentioning
confidence: 99%
“…Recently, an absorbable unidirectional barbed suture has become available (V-Loc™180, Covidien, Mansfield, MA) ( Figure-1). This suture has been used for skin and soft tissue closures, gynecologic procedures, and bowel anastomosis in a porcine model (6)(7)(8). Anastomoses using standard monofilament for running closure requires frequent re-tightening, with some surgeons relying on the assistant to follow the suture to maintain tension.…”
mentioning
confidence: 99%
“…To date, there have been no suitable devices for peritoneal closure for beginners. V-Loc has been available only recently; therefore, only a few reports on intra-abdominal usage are available [5] . In the present study, we investigated the use of V-Loc to assess the potential simplification of the technically difficult peritoneal closure in herniorrhaphy.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Subsequent studies on porcine enteric anastomoses have demonstrated closure equivalence with maxon (monofilament polyglyconate), but with faster anastomosis times. 12 Since the initial porcine study by Weld and colleagues, which assessed self-anchoring suture (SAS) material for urinary tract reconstruction, two recent publications have emerged assessing barbed suture for RARP VUA demonstrating feasibility and increased efficiency. 13,14 These small series, however, used separate sutures for PR and VUA.…”
Section: Introductionmentioning
confidence: 99%